MUSIC THERAPY PRACTICE TO REDUCE ANGER FOR ELDERLY IN A GOVERNMENT NURSING HOME - Monica Unsri; Monty P. Satiadarma; Untung Subroto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2017)
This research is aimed to the practice of music group therapy to reduce anger for elderly in a government nursing home. Anger can be defined as a psychobiological emotional state or condition that consists of feelings that vary in intensity from mild irritation or annoyance to intense fury and rage, accompanied by activation and of neuroendocrine processes and arousal of the autonomic nervous system. While music therapy is the clinical and evidence-based use of music interventions to accomplish individualized goals within a therapeutic relationship. The research use pre-test post-test one group design. Beside using the interview method, pre-test and post-test also been involved to measure the anger intensity of the participants against anger before and after the intervention. There are three participants. The result showed that music group therapy could reduce the anger of the elderly living in government nursing home.